Could Microwave Glazing Be Considered as an Alternative to Conventional Surface Finishing Methods of Ceramic Materials in Terms of Color Stability - Şanal, F.A.; Kurt, M. (Quintessence Publishing Co. Inc. contact@quintbook.com, 2020)
Purpose: To examine microwave heating for the purpose of ceramic glazing as an alternative to conventional methods in terms of color stability. Materials and Methods: Thirty disk-shaped specimens (11 x 2 mm) of VITA VM 9, VITA VM 13, VITA VMK 95, and IPS e. max Ceram veneers were prepared (n = 30 each). The specimens were further divided into three subgroups according to surface finishing procedure (polishing, conventional oven glazing, or microwave glazing [n = 10 each]). The related surface finishing procedure was applied according to the manufacturers' instructions. Color differences (ΔE) of the ceramic samples stored in a coffee solution at 37°C for 168 hours were determined using spectrophotometry. Data were analyzed using two-way ANOVA. The group differences were analyzed using Tukey HSD test. Results: Microwave-glazed specimens showed similar ΔE values to conventionally glazed specimens for the tested ceramics (P >.05). Polished specimens showed higher ΔE values than glazed specimens for the investigated ceramic materials, and the difference was significant for VITA VMK 95 and Vita VM9 (P ≤.05). Conclusion: Microwave glazing has the advantage of decreasing glazing time to a few minutes and could be considered as an alternative method to conventional oven glazing and polishing with respect to color stability. Int J Prosthodont 2020;33:328-332. doi: 10.11607/ijp.6412. © 2020 by Quintessence Publishing Co Inc.